Independence of Mediation Institutions as an Alternative to Settlement Divorce Disputes in Indonesia - Sri Turatmiyah; Joni Emirzon; Annalisa Yahanan (Faculty of Law, Universitas Pekalongan, 2025)
This study examines divorce dispute mediation that is currently integrated into the court process according to Supreme Court Regulation (PERMA) No. 1 of 2016, with the aim of reformulating mediation into an independent institution separate from litigation to be more effective and aligned with Pancasila values, as well as providing regulatory recommendations and institutional support to the Government. The method used is a qualitative study with a normative analysis approach toward regulations and practices of divorce mediation in religious courts. The research results show that mediation regulated in PERMA has deviated significantly from the spirit of mediation, namely as an alternative dispute resolution. The mediation that has been implemented so far accommodates the provisions of Article 131 HIR and Article 154 R.Bg, namely the empowerment of peace institutions. However, the way this mediation is carried out does not align with the core principles of Indonesia, which include Pancasila emphasizing open discussion to achieve agreement. It is believed that the mediation process outlined in PERMA No. 1 of 2016 is more akin to a legal procedure that parties involved in divorce cases are required to follow in order to resolve their disputes. The implication of this research is the need for legal reformulation of divorce mediation that separates mediation from court litigation processes, by establishing an independent mediation institution supported by the government. This is expected to optimize the function of mediation as a dispute resolution method that is more effective, efficient, and in accordance with Pancasila values.